2015
DOI: 10.1007/s12264-015-1565-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of extraversion-introversion

Abstract: Neuroimaging techniques such as functional magnetic resonance imaging and positron emission tomography have provided an unprecedented neurobiological perspective for research on personality traits . Evidence from task-related neuroimaging has shown that extraversion is associated with activations in regions of the anterior cingulate cortex, dorsolateral prefrontal cortex, middle temporal gyrus and the amygdala. Currently, resting-state neuroimaging is being widely used in cognitive neuroscience. Initial explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 61 publications
(173 reference statements)
3
27
0
Order By: Relevance
“…The neuroticism trait crossmatches with T&P self-criticism and rejection sensitivity traits, and introversion crossmatches with the T&P personal reserve trait 27. Neuroimaging studies have demonstrated that degree of introversion is associated with activations in regions of the anterior cingulate cortex, dorsolateral prefrontal cortex, middle temporal gyrus, and the amygdala 3336. Yet, the process underlying the predictive association between personality traits and treatment outcome is not entirely clear; further understanding of lower-order dimensions and their neurobiological background may contribute to making further progress in elucidating the predictors of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroticism trait crossmatches with T&P self-criticism and rejection sensitivity traits, and introversion crossmatches with the T&P personal reserve trait 27. Neuroimaging studies have demonstrated that degree of introversion is associated with activations in regions of the anterior cingulate cortex, dorsolateral prefrontal cortex, middle temporal gyrus, and the amygdala 3336. Yet, the process underlying the predictive association between personality traits and treatment outcome is not entirely clear; further understanding of lower-order dimensions and their neurobiological background may contribute to making further progress in elucidating the predictors of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Extraversion has been linked to regions responding to reward-related stimuli like nucleus accumbens, striatum, amygdala, and orbitofrontal cortex (DeYoung et al 2010b; Adelstein et al 2011; Pang et al 2016, c.f. ; Lei et al 2015). Conscientiousness has been related to the lateral prefrontal cortex (Asahi et al 2004; Passamonti et al 2006; DeYoung et al 2010; Kunisato et al 2011), deputed to the planning, following complex rule and voluntarily control of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the research focused on the assessment of personality 36 based on the analysis of EEG data in the resting state has not reached consistent 37 conclusions. While some papers reported a successful assessment [17], others concluded 38 that resting state features could not be used [18]. Based on the previous studies, we 39 hypothesize that the features associated with personality traits are more pronounced 40 during cognitive activity.…”
Section: Introductionmentioning
confidence: 86%